Cytotoxic activity of extracts from the four lichen species against human cancer cells lines - Khramchankova, Volga M.; Matveyenkau, Matsvei V. (Journal of the Belarusian State University. Ecology, 2019)
In vitro evaluated the ability of acetone and ethanol extract from lichen species Hypogymnia physodes, Evernia prunastri, Ramalina pollinaria and Cladonia arbuscula to inhibit the viability of human cancer and stable cell lines. Extracts from Hypogymnia physodes, Evernia prunastri and Cladonia arbuscula were cytotoxic against tumor cell lines A-549, HeP-2C and MCF-7, as well as against non-tumorigenic human epithelial cell line HaCAT. The lichen extract from Ramalina pollinaria was nontoxic against human cancer cell lines, as well as against human keratinocyte cells HaCAT. The dynamics of cell viability decrease lines is described by S-shaped curves. Specificity of the cytotoxic effect of extracts from lichens Hypogymnia physodes, Evernia prunastri and Cladonia arbuscula was manifested with respect to the MCF-7 cell line (IC50 = 3,86÷7,06 μg/ml; SI = 1,44÷5,05). For cell cultures A-549 and HeP-2C, extracts with a pronounced toxic effect (IC50 < 30,0 μg/ml) did not differ in specificity (SI ≤ 1,0). The extract from Ramalina pollinaria at IC50 = 40,55÷49,37 μg/ml was characterized by pronounced specificity for the cultures of tumor cells (SI = 1,46÷1,77).